Bioaccessibility as a determining factor in the bioavailability and toxicokinetics of cadmium compounds. (November 2021) - Poland, Craig A.; Lombaert, Noömi; Mackie, Carol; Renard, Alain; Sinha, Parikhit; Verougstraete, Violaine; Lourens, Nicky J.J.
Highlights: Cadmium toxicity arises from the bioavailability and bioaccumulation of Cd 2+ ions. Different cadmium compounds show different levels of bioavailability. Ion availability for absorption is determined by its release in biological fluids. This release (bioaccessibility) can be measured and used to inform in vivo studies. In vitro analysis of bioaccessibility supports the estimation of bioavailability and potential for target tissue toxicity. Abstract: Cadmium toxicity occurs where there is absorption and accumulation of cadmium ions (Cd 2+ ) in tissues beyond tolerable levels. Significant differences in the release of Cd 2+ from cadmium compounds in biological fluids, like gastric fluid, may indicate differences in bioavailability and absorption. This means that direct read-across from high solubility cadmium compounds to lower solubility compounds may not accurately reflect potential hazards. Here, the relative bioaccessibility in gastric fluid of cadmium telluride and cadmium chloride was evaluated using in vitro bioelution tests whilst the toxicokinetic behavior of these two compounds were compared after dietary administration for 90 days in male and female Wistar Han rats following OECD TG 408. Cadmium chloride was highly bioaccessible, whilst cadmium telluride showed low solubility in simulated gastric fluid (90 % and 1.5 % bioaccessibility, respectively). This difference in bioaccessibility was also reflected by a difference in bioavailability as shown by the difference in the liver and kidney concentrations of cadmium after repeat oral exposure. Feeding at doses of 750 and 1500 ppm of cadmium telluride did not result in tissue cadmium levels above the lower limit of quantification (LLOQ). In contrast, feeding with a lower test substance concentration yet higher concentration of bioaccessible cadmium (30 ppm cadmium chloride) resulted in tissue accumulation of cadmium. Only slight, non-adverse changes in hematology and clinical chemistry parameters were seen at these doses, indicating an absence of significant cadmium mediated toxicity towards target organs (kidney and liver), reflected in minimal cadmium accumulation in these organs. This study demonstrates that bioelution tests can help determine the bioaccessibility of cadmium, which can be used to estimate the potential for target tissue toxicity based on known toxicokinetic profiles and threshold levels for cadmium toxicity, while reducing and refining animal testing.